Extent and glacial history of the Cordilleran Ice Sheet in northwest Montana: using OSL to date glacial sediments from the southeastern Flathead Lobe - Shukla, Vidhesh (Kansas State University, 2023)
This thesis investigates glacial sediments in the Flathead Valley, Polson, Montana that were deposited during the last glacial period (~115,000 – 11,700 years ago). Research objectives were to reconstruct the glacial history and timing of the furthest southeasterly extent of the Cordilleran Ice Sheet (CIS) at the Flathead Lobe in northwestern Montana and to assess the viability of luminescence dating of sediments in glacial environments. The advance and retreat of past ice sheets can shed new light on our understanding of the cryosphere. The CIS was one of the major late Quaternary ice sheets. The CIS initially developed in southern Alaska but spread south during the Fraser Glaciation. The maximum extent of the CIS in the west is represented by the Juan de Fuca Lobe (17.5 ka) in Washington and in the east, it is represented by Flathead Lobe in Montana. The Flathead Lobe inhabited the Rocky Mountain Trench and terminated near the north end of the Mission Valley around Polson, Montana. The chronology of the western lobes of the CIS have received much attention, but not the easternmost lobes. There are only a few widely applicable and precise methods to date Quaternary landforms and sediments, and recent developments in optically stimulated luminescence (OSL) dating provide us with an opportunity to date a broad range of late Quaternary sediments. This thesis focused on the sedimentology and stratigraphy of surficial and older glacial sequences in the Flathead Valley and used OSL dating to establish age control for the deposits. Fieldwork for the project was conducted during the summer of 2021, during which time the sites in the vicinity of Flathead Lake and Polson, Montana, representing Quaternary moraine deposits, glacial lake deposits, glacial lake outwash, and glacial till from localities consistent with the position of the furthest extent of the Flathead Lobe were visited, described, and sampled. Updated digital elevation models were created to provide a comprehensive and detailed representation of the features associated with the terminal extent of the Flathead Lobe. Chronological constraints on the terminal extent of the CIS were obtained through small aliquot dating luminescence analysis of quartz from the glacial sediments. Ages from the Polson Moraine span from 15.0 ± 1.0 ka to 52.1 ± 2.9 ka, while those from the Elmo Moraine range from 45.4 ± 1.5 ka to 50.1 ± 1.5 ka. This study used a combination of OSL geochronology, glacial geomorphology, and geospatial studies to determine the Polson Moraine of the Flathead Lobe as the maximum extent of the CIS. Seven samples were collected from various depositional environments to provide a comprehensive understanding of the glacial history and sedimentary processes that took place. Limitations to small-aliquot OSL dating of quartz sediments from the Polson and Elmo Moraine were encountered. These limitations were reflected in age overestimates except for Polson-03; limitations are most likely attributed to incomplete daylight bleaching of the quartz grains prior to deposition. Preliminary results from the Flathead Lobe suggest that bleaching potential of these glacial sediments is influenced by facies and depositional environment.
Keywords: Flathead Lobe; Geochronology; Quaternary geology; OSL dating; Geomorphology; Glaciology